The Number of Idempotents in Commutative Group Rings of Prime Characteristic - Danchev, P. V. (Sarajevo Journal of Mathematics, 2024)
Suppose R is a commutative unitary ring of prime characteristic p and G is a multiplicative abelian group. The cardinality of the set id(RG) consisting of all idempotent elements in the group ring RG, is explicitly calculated only in terms associated with R and G or their sections. 2010 Mathematics Subject Classification. 16S34, 16U60, 20K20, 20K21